Optimal management of supply disruptions when contracting with unreliable, risk-averse, suppliers - Sarah Parlane; Yingyi Tsai (University College Dublin, UCD School of Economics, 2017)
This paper investigates the optimal management of supply disruptions by a manufacturer who uses order inflation and/or investments in process reliability when contracting two risk-averse suppliers. We consider that these investments can be subject to moral hazard. Technically we solve a newsvendor optimization problem using a random capacity model of disruption. In such a model, the order size does not affect the average production but impacts the probability of disruption. When investments are verifiable we show that the manufacturer is more inclined to invest in the suppliers' reliability and then refrain from using order inflation when the suppliers' production costs and the cost of disposing of unwanted inputs are large. When investments are not verifiable we show that the order sizes can be used strategically as incentive devises due to the suppliers' sensitivity to payoff dispersion. We show that the manufacturer does not always increase his reliance on order inflation and face less reliable suppliers once we introduce moral hazard. In some instances he induces suppliers to undertake larger investments in reliability by increasing the order size. In other instances he is able to reduce his reliance on order inflation.
Keywords: D86; L24; M11; 330; newsvendor optimisation; moral hazard; random capacity model